Synthesis of chalcones and their uses as potential pharmacological agents: Review article (Journal of Pharma Insights and Research, 2023)
Chalcone is an α,β-unsaturated ketone and serves as the fundamental framework for numerous significant biological molecules. Due to the existence of α,β-unsaturated ketone functionality, the derivatives of chalcone exhibit enormous therapeutic value, including inhibition of enzymes, anti-bacterial, anti-cancer, anti-inflammatory, anti-fungal, anti-malarial, anti-protozoal, and anti-filarial action. A type of open-chain flavonoids known as chalcone can be produced synthetically as well as via biosynthesis in plants. The Claisen-Schmidt condensation reaction and the additional modern-day invention known as aldol condensation may both be used to produce the simplest chalcone by reacting benzaldehyde and an active methylene ketone in homogenous conditions. 1,3-diaryl-2-propen-1-one, also referred to as chalconoid, is a chemical building block shared by all chalcone compounds. There are two isomers: trans and cis, with trans having greater thermodynamic stability than the cis isomer. By adding various heterocyclic moieties to the structural framework of chalcones, after conducting many investigations, nearly all of them revealed different bioactivities. Chalcones produced from naturally occurring substances are homocyclic and have less bioactivity than compounds made using heterocyclic building blocks. Therefore, the capacity to structurally change chalcones by synthesis provides superior benefits than using natural chalcones, including higher yields, easier handling, cost-effectiveness, and many other things. Despite the reality that the Chalcones have undergone in-depth research, the precise mechanisms of action behind the many biological actions of the chalcones are currently insufficiently understood.